Pityriasis amiantacea: a study of seven cases - Gustavo Moreira Amorim; Nurimar Conceição Fernandes (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Pityriasis amiantacea was first described in 1832. The disease may be secondary to any skin condition that primarily affects the scalp, including seborrheic dermatitis. Its pathogenesis remains uncertain. We aim to analyze the epidemiological and clinical profiles of patients with pityriasis amiantacea to better understand treatment responses. We identified seven cases of pityriasis amiantacea and a female predominance in a sample of 63 pediatric patients with seborrheic dermatitis followed for an average of 20.4 months. We reported a mean age of 5.9 years. Five patients were female, with a mean age of 9 years. All patients were successfully treated with topic ketoconazole.